Study on the influence of various base agents in K2TiF6 hydrolysis on morphology, structure and photocatalytic activity of TiO2 - Lam, Nguyen Tan; Dieu Cam, Nguyen Thi; Hung, Nguyen Phi; Noi, Nguyen Van (Vietnam Journal of Chemistry, 2017)
K2TiF6 was hydrolyzed by various base agents including solutions of NH3, NaOH, and KOH at the same concentration of 3 M. TiO2 material was obtained after filtering, washing, drying and calcination at 500 °C of Ti(OH)4 precipitate. The experimental results showed that there was a significant influence of base agent nature on the morphology, structure, surface area of TiO2 product. Using NH3 agent could obtain uniform TiO2 particles with about 15 nm in size and surface area of 98.93 m2.g-1, while using NaOH or KOH led to TiO2 with varying particle sizes (in the range of 15-500 nm), and decreasing surface area (less than 20 m2.g-1). The nature of base agent also significantly influenced photocatalytic activity of TiO2 product for methylene blue (MB) decomposition. The prepared TiO2 from NH3-using process showed the highest phtocatalytic activity in comparison with TiO2 from KOH/NaOH-using process or commercial TiO2 (P25). Keywords. K2TiF6, TiO2, Ti(OH)4, photocatalyst.